Предмет: Алгебра,
автор: lisitsynanasti
SOS!!!Помогите пожалуйста решить срочно!!!!
Преобразуйте выражение в многочлен
(x+y+z)(x+y-z)
(x-y+z)(x-y-z)
(x-y+z)(x+y+z)
Ответы
Автор ответа:
0
(x+y+z)(x+y-z)=X²+xy-xz+yx+y²-yz+zx+zy-z²=X²+Y²-Z²+2XY
(x-y+z)(x-y-z)=X²-yx-zx-yx-y²+zy+zx-zy-z²=X²+Y²-Z²-2YX
(x-y+z)(x+y+z)=X²+XY+XZ-YX-Y²-YZ+ZX+ZY+Z²=X²-Y²+Z²+2ZX
(x-y+z)(x-y-z)=X²-yx-zx-yx-y²+zy+zx-zy-z²=X²+Y²-Z²-2YX
(x-y+z)(x+y+z)=X²+XY+XZ-YX-Y²-YZ+ZX+ZY+Z²=X²-Y²+Z²+2ZX
Похожие вопросы
Предмет: Математика,
автор: slavik24SV
Предмет: ОБЖ,
автор: arturloginov
Предмет: Қазақ тiлi,
автор: Katya1Zyryanova
Предмет: Геометрия,
автор: МашаБоброва